2018
DOI: 10.3390/vetsci5010017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Practices Regarding Cystic Echinococcosis among Livestock Farmers in Basrah Province, Iraq

Abstract: Cystic echinococcosis (CE) is an endemic neglected parasitic zoonosis in many of the countries of the Middle East. The disease poses a remarkable economic burden for both animals and humans. In this study, we conducted a questionnaire survey among livestock farmers in Basrah province, southern Iraq, in order to evaluate their knowledge and awareness about CE, and to understand some of the risky practices that could contribute to spread and persistence of such disease. Of the interviewed participants (N = 314),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…WHO Eastern Mediterranean Region (EMRO), which includes most of the Middle East and North Africa (MENA), is one of the most ancient foci of the domestic cycle of CE and is recognized as one of the major hotspots of CE [4,5]. The stable endemicity of CE in this region is largely associated with several factors, including diverse intermediate host species (sheep, goats, camels, cattle, buffalos, and wild pigs), traditional farming and livestock husbandry, poor quality and/or unregulated abattoirs, widespread practice of home slaughter, high consumption of raw vegetables, large numbers of stray dogs, and low level of public awareness about CE transmission [1,6,7]. CE imposes substantial costs to low-and middle-income countries that is estimated at 0.01% to 0.04% of nation's gross domestic product (GDP) [8].…”
mentioning
confidence: 99%
“…WHO Eastern Mediterranean Region (EMRO), which includes most of the Middle East and North Africa (MENA), is one of the most ancient foci of the domestic cycle of CE and is recognized as one of the major hotspots of CE [4,5]. The stable endemicity of CE in this region is largely associated with several factors, including diverse intermediate host species (sheep, goats, camels, cattle, buffalos, and wild pigs), traditional farming and livestock husbandry, poor quality and/or unregulated abattoirs, widespread practice of home slaughter, high consumption of raw vegetables, large numbers of stray dogs, and low level of public awareness about CE transmission [1,6,7]. CE imposes substantial costs to low-and middle-income countries that is estimated at 0.01% to 0.04% of nation's gross domestic product (GDP) [8].…”
mentioning
confidence: 99%
“…Similarly, a study conducted in Qinghai Province, China demonstrated that humans with alveolar echinococcosis were more likely to have a lower educational level compared to non-infected controls [60]. Such findings highlight the need for developing and implementing educational campaigns suitable for dog-owners in Basrah [35]. A key component of an educational campaign should be improving the knowledge of farmers and dog owners about CE and the parasite's life cycle.…”
Section: Discussionmentioning
confidence: 96%
“…The study was performed from March to July 2016. Of 314 livestock owners who were surveyed to assess their knowledge, awareness and practices toward CE [35], 86 owned at least one dog (total of 122 dogs from 16 villages in the six districts of Abu Al-Kasib, Al-Midaina, Al-Qurnah, Al-Zubair, Shat AleArab, and Al-Basrah. A further questionnaire was administered to the 86 dog-owners and included questions on management practices adopted (whether the dog was restrained or not; administered anthelmintics; fed offal; and how faeces from the dogs were disposed of; and the age and sex of the dogs).…”
Section: Study Design Questionnaire Survey and Sampling Of Dogsmentioning
confidence: 99%
“…• Prevent dogs from feeding on infected sheep [19,33] • The limiting of home cattle butchers [34] • Avoidance of any food or water that may be contaminated by dog's feces [25,35] • Handwashing with soap and water after handling dogs [25] • Vaccination of cattle with EG95 vaccine to interrupt the life cycle of E. granulosus [36][37][38] • Dogs can be terminated using praziquantel every 6 weeks [37,39] • Not to contact with wild animals such as foxes and stray dogs [25].…”
Section: Control and Preventionmentioning
confidence: 99%